Supportive supervision of nurses and its impact on healthcare access in sub-Saharan Africa - Serapelwane, Maserapelo; Kovane, Gaotswake; Bam, Nokwanda (Health SA = SA Gesondheid, 2025)
Background: Supportive supervision of nurses remains a concern globally, particularly in sub-Saharan countries. It involves providing guidance, resources and encouragement to nurses to deliver high-quality patient care. Aim: This study aimed to systematically review literature regarding supportive supervision of nurses and its impact on healthcare access. Method: The study used a systematic review method, guided by the PICOT (Patient/Population, Intervention, Comparison, Outcome and Timeframe), which framed the review question. The systematic search was based on articles written in English from 2013 to 2023. Databases used for locating the articles were: Web of Science, Google Scholar, Scopus, EBSCOhost, SA ePublication, PubMed, Medline, PubMed and Science Direct. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist was used to report the identified studies, while the quality of studies meeting the review criteria was assessed using the 11 questions from the Joanna Briggs Institute (JBI) critical appraisal checklist. Results: A total of 274 articles were identified, and data were extracted from five articles that met eligibility criteria. The study showed that supportive supervision of nurses improves access to healthcare by boosting job satisfaction and clinical competency. The negative impact of the lack of supportive supervision of nurses was related to declined performance because of a lack of policies or guidelines and dictatorial supervision. Conclusion: It is evident from the findings that supportive supervision of nurses enhances access to healthcare, whereas its absence negatively affects it. Contribution: The study provided new insights into how supportive supervision of nurses influences access to healthcare.